„Ku nowym czynom, ukochany mężu...” O Stukasach Karla Rittera - Kozłowski, Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
Karl Ritter’s film Stukas has been the subject of numerous analyses centred on issues such as propaganda (Rother), Nazi films about aviators (Gwóźdź), war and music (Vaget). This article situates itself within the general discussion of art and politics in the Third Reich (Mungen, Pyta, Vaget, Werr). It starts from Goebbels’ speech on February, 15 1941 at the Reichsfilmkammer and attempts to look at Ritter’s film from the perspective of Richard Wagner’s music and the Bayreuth festival theatre as an important cultural and intermedial symbol of Nazi Germany. Further, it aims to juxtapose the film plot with the meaning of the instrumental prelude ‘Siegfrieds Rheinfahrt’ that precedes Act I of Twilight of the Gods, showing that the theatrical experience of the apathetic Lieutenant Vide allows him to discover dormant layers of his own heroism. Driven by this discovery, he is able – like Siegfried alongside his pillar Brünnhilde – to undertake therefore new challenges and conquer England with his fellow pilots. It shall be argued that the Third Reich propaganda concept of Bayreuth and the Festspielhaus locks in with this thesis. It is here, with the support of the hospital sisters, that soldiers can recover fully. Nevertheless, it is by no means medications and systematic therapies that play the part of Asclepius, but the power of Wagner’s music (rooted in mythology).